Pengaruh Subsidi Pupuk, Luas Lahan, Terhadap Biaya Produksi dan Pendapatan Petani Padi Di Desa Jatiluwih, Kecamatan Penebel, Kabupaten Tabanan - Setyawati, Ni Made Ayu Sita; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
Agliculture sector is a sector that is very important role in the economy of most of the countries that are developing. Agricultural development needs to get better attention, despite the priority at the discretion of industrialization had been dropped, but the agricultural sector has the ability to generate increased revenue. The research have a main purpose to indentify the impact of fertilizer subsidies, landsize, to costs of production and farmer’s income in Jatiluwih, Penebel, Tabanan. The data is obtained by doing depth interview to use kuisioner. The amount of sample is 80 farmers, the technique that used for sampling is stratified random sampling. This research using path analysis to analyze direct relation between one to other variables and sobel analysis is to analyze undirect relation with intervening variable. Depend on this research we know that fertilizer subsidies have negative impact to costs of production, landsize have positive and significant impact to costs of production, fertilizer subsidies, landsize, and costs of production have positive and significant impact to farmer’s income. Fertilizer subsidies and landsize which have undirect impact with farmer’s income through costs of production.   Keywords: Fertilizer Subsidies, Landsize, Costs Of Production, and Farmer’s Income